Application of bioelectric effect to reduce the antibiotic resistance of subgingival plaque biofilm: An in vitro study - Padmini Hari; Kranthi Raja Kacharaju; Naveen Anumala; Krishnanjaneya Reddy Pathakota; Jayakumar Avula (Wolters Kluwer Medknow Publications, 2018)
Context: Biofilms are known for their antimicrobial resistance, and so is the subgingival plaque biofilm, the primary etiologic factor for periodontal infections. Aims: The objective of this study is to investigate if the subgingival plaque biofilm resistance can be reduced using doxycycline in the presence of low-intensity electric field (bioelectric effect). Settings and Design: The study was an in vitro microbiological study. Materials and Methods: Subgingival plaque samples from chronic periodontitis patients were collected to grow subgingival plaque biofilms on hydroxyapatite disks. Hydroxyapatite disks with the plaque biofilms from each patient were divided into four groups: (i) No intervention - control, (ii) current alone - CU; (iii) doxycycline - AB, and (iv) combined treatment - CU + AB. After respective treatments, the disks were anaerobically incubated for 48 h, the biofilm was dispersed and subcultured and colony-forming unit/mL was estimated in all the four groups. Statistical Analysis: Statistical analysis was done using Mann-Whitney and Kruskal-Wallis tests for intergroup comparisons. T-test was done to assess the difference in current flow between the groups CU and CU + AB. Results: All the three treatment modalities showed antibacterial effect. Application of current alone resulted in reduced bacterial growth than control group. Doxycycline alone resulted in reduction in bacterial counts better than control and current alone groups. The combination treatment showed greatest inhibition of bacterial colonies. Conclusion: The ability of doxycycline antibiotic in inhibiting plaque biofilm was significantly enhanced by application of a weak electric field (5 volts for 2 min).